ANALISIS FIKIH SISTEM PEMBIAYAAN MUDHARABAH DALAM PRAKTIK DAN PERATURAN PERUNDANG–UNDANGAN PERBANKAN SYARI’AH - Nining Sri Wahyuni (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
The aims of this research are to give the understanding about comparation of System Capital Mudharabah Costing in practice of Shariah Banking with Fiqh, to give understanding about the suitable of the Mudharabah practice in Shariah Banking with the rale of law Shariah Banking, and to give the understanding of the appropriate of Mudharabah practice  in the rale of law Shariah Banking with Fiqh. To give the explanation above through a research with used normative and sociology method and instrument for collecting data are document data given from Mualamah Bangking in Medan. It is showed the practice of the Capital Mudharabah Collecting in Shariah Banking is still not suitable to Shariah principle in Fiqh